Pastoralist landscapes as multifunctional systems of interaction between people and nature. The case of Tropoja, Albania - Doempke S. (Pastoralisme méditerranéen : patrimoine culturel et paysager et développement durable, 2010)
This article discusses the multifunctionality of mountain pastoral areas, with their economic, ecological, cultural and even spiritual functions. These remarks are based on field observations in the Tropoja region in northern Albania. They show that pastoralism is both the cornerstone of the Albanian identity and a good example of the combination of globalization and bio-regionalism.
2. Réunion Thématique d'Experts sur le Pastoralisme Méditerranéen, 2009/11/12-14, Tirana (Albanie)